Food and feeding habits of Labeo dussumieri (Val.) of the river Pampa - Kurup, B Madhusoodana (Indian Journal of Fisheries, 2011)
Food plays a vital role in growth andtherefore, fish migration and abundance ofstocks are also related to availability of food.L. dussumieri is the only species of Labeoindigenous to Kerala waters (Kurup andKuriakose 1991) and hitherto no attempt hasso far been made to study the food and feedinghabits of this species, though informationon similar aspects of related species areavailable (Oas and Moitra 1956, Bhatnagarand Karamchandani 1970, Vinci andSupnan 1981).